Antibodies at work in the time of SARS-CoV-2 (2020)
Even after a decade of continuous emergence of coronaviruses, there aren’t any licenced vaccines or therapeutics against the deadly infection. The age-old passive immunization with protective antibodies to neutralize the virus is one of the strategies for emergency prophylaxis and therapy for COVID-19. In this review, we discuss the up-to-date advances in immunebased therapy for COVID-19. The use of convalescent plasma therapy as the first line of defences to treat SARS-CoV-2 infection has been established with encouraging results. Monoclonal antibodies (mAbs) that bind to the receptor-binding domain (RBD) of SARSCoV-2 spike (S) protein or blocking the interaction between SARS-CoV-2 RBD and human angiotensin-converting enzyme 2 (hACE2) receptor have been found very promising as the countermeasure to tackle the SARS-CoV-2 infection, though clinical trials are underway. Considering the counterproductive antibody-dependent enhancement of the virus, the mAbs therapy that is safe and efficacious even in people with an underlying condition will be a significant breakthrough. The emerging immunotherapeutic interventions using nanobodies and cellular immunotherapy are also the promising avenues to tackle the COVID-19 pandemic. We also discuss the implication of mAbs against mediators of cytokine storm syndrome to modify the immune response of COVID-19 patients, thus reducing the fatality rate of COVID-19 infection.